Methaphysics - Tabanli, Mustafa (New Jersey : Everest Production, 2008)
Explores Metaphysics is a traditional branch of philosophy concerned with explaining the fundamental nature of being and the world
Executive producer, Nasuhi yurt.
Host : MaryLynn Schiavi
Keywords: Metaphysics